Exploring the Digital Frontier Online Sellers’ Experiences in E-commerce Landscape (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
The researchers utilized a qualitative approach, employing transcendental phenomenology to examine the experiences of the respondents through their perspective. The researchers gathered data from active live sellers on Facebook. Unstructured interviews were conducted.The findings reveal that the informants experience challenges such as logistics and customer service, time management, and work-life balance. To overcome these hurdles, the informants use strategies like social media engagement, referral networks, and customer rewards. The researchers assert that the entrepreneurs should continue to explore online selling as a new mode of marketing their products because it offers unparalleled opportunities for market expansion, customer engagement, and business growth. Moreover, the adaptive strategies demonstrated by the informants underscore the resilience and potential for success within the e-commerce landscape, affirming the viability of online platforms as essential avenues for entrepreneurial endeavors in the contemporary market milieu.
Keywords: online sellers; e-commerce landscape; business challenges and opportunities